2020
DOI: 10.1016/j.celrep.2020.108205
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Csy4-Mediated Editing of Rotavirus Double-Stranded RNA Genome

Abstract: CRISPR-nucleases have been widely applied for editing cellular and viral genomes, but nuclease-mediated genome editing of double-stranded RNA (dsRNA) viruses has not yet been reported. Here, by engineering CRISPR-Csy4 nuclease to localize to rotavirus viral factories, we achieve the nuclease-mediated genome editing of rotavirus, an important human and livestock pathogen with a multisegmented dsRNA genome. Rotavirus replication intermediates cleaved by Csy4 is edited through the formation of precise deletions i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 51 publications
1
30
0
Order By: Relevance
“…This implies that the unique viroplasmic condensate composition must be maintained through enrichment of cognate RNA-binding viral proteins. Remarkably, targeting the RV RNP condensates by a catalytically active Cas6f/Csy4 endonuclease fused to NSP5 results in the viral RNA genome editing that occurs within these condensates 22 , further confirming the essential role of these RNP condensates in the RV transcript selection and enrichment. The UDEx-FISH analysis of single cells revealed that the apparent stoichiometries of viroplasm-enriched and cytoplasmicallylocalised RV transcripts were different, suggesting that the observed RNA partitioning mechanism may also contribute to the efficient stoichiometric enrichment of eleven non-identical viral transcripts in these condensates.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…This implies that the unique viroplasmic condensate composition must be maintained through enrichment of cognate RNA-binding viral proteins. Remarkably, targeting the RV RNP condensates by a catalytically active Cas6f/Csy4 endonuclease fused to NSP5 results in the viral RNA genome editing that occurs within these condensates 22 , further confirming the essential role of these RNP condensates in the RV transcript selection and enrichment. The UDEx-FISH analysis of single cells revealed that the apparent stoichiometries of viroplasm-enriched and cytoplasmicallylocalised RV transcripts were different, suggesting that the observed RNA partitioning mechanism may also contribute to the efficient stoichiometric enrichment of eleven non-identical viral transcripts in these condensates.…”
Section: Discussionmentioning
confidence: 73%
“…MA104-shRNA-NSP2 cell line was generated using the PiggyBac system. Briefly, 10 5 MA104 cells were co-transfected with the plasmid pCMV-HyPBase encoding the hyperactive variant of PiggyBac transposase 56,57,22 along with the plasmid pPB[shRNA]-EGFP:T2A:Puro-U6 harbouring shRNA targeting RVA NSP2 gene using Lipofectamine 3000 (Sigma-Aldrich), following the manufacturer's instructions. The cells were maintained in DMEM supplemented with 10% FBS for 3 days, and then the cells were subjected to selection in the presence of 5 μg/ml puromycin (Sigma-Aldrich) for 4 days, prior to further selection by FACS sorting for EGFP expression.…”
Section: Generation Of Stable Cell Linesmentioning
confidence: 99%
See 2 more Smart Citations
“…We next assessed whether these four VP4-BAP proteins could assemble into infectious rotavirus particles and support virus replication. For this purpose, we took advantage of a newly developed reverse genetics system to rescue recombinant rotavirus (rRV) harboring a genetically modified genome segment 4 (gs4) encoding the different VP4-BAP proteins (gs4-BAP) (38)(39)(40)(41).…”
Section: Production and Characterization Of Recombinant Rotavirus Expressing Vp4-bap Protein Asmentioning
confidence: 99%